Comparison of Colorimetric and HPLC Methods for Determination of δ-Aminolevulinic Acid in Urine with Reference to Dose-Response Relationship in Occupational Exposure to Lead - OKAMOTO, Satoru; TAKADA, Shiro; FUKUI, Yoshinari; IKEDA, Masayuki; MIKI, Mieko; UKAI, Hirohiko (Industrial Health, 2005)
Both traditional colorimetry and recently developed HPLC-fluorometry have been in use for determination of δ-aminolevulinic acid in urine (ALA-U), an effect marker of occupational exposure to lead (Pb). The present study was initiated to compare the values by the two methods on an epidemiology basis among workers occupationally exposed to lead (Pb), to estimate quantitatively the colorimetry-associated increment over the values by the HPLC method, to evaluate ALA-U determination in occupational health service for Pb-exposed workers, and to identify a critical Pb-B to induce an elevation in ALA-U. For this purpose, blood and urine samples were collected from three groups of Pb-exposed workers (both men and women in combination, including smokers) and analyzed for Pb in blood (Pb-B; measured in all subjects) and ALA-U (by colorimetry or HPLC), i.e., Group 1 (164 subjects with urinalysis by the two methods), Group 2 (2,923 subjects by colorimetry), and Group 3 (2,540 subjects by HPLC). ALA-U when measured by colorimetry was higher than the values by HPLC, and that the mean difference on a group basis was 1.4 mg/l (in a range of 1.1 to 1.8 mg/l), irrespective of Pb-B levels. It was also found that the increase in ALA-U was small when Pb-B was relatively low (e.g., ≤40 μg/100 ml), and that the increase on a group basis in response to an increase in Pb-B from 5 to 40 μg/100 ml was as small as ≤0.6 mg/l. Thus, ALA-U appeared to be not a sensitive marker of Pb effects at low Pb-B levels. ALA-U however increased substantially with a point of inflection at the Pb-B level of about 17-34 μg/100 ml. Thus it was concluded that ALA-U as measured by colorimetry is greater than ALA-U by HPLC by 1.4 mg/l on average irrespective of intensity of Pb-exposure, which may induce bias in evaluation of health effect, and that ALA-U levels will increase when Pb-B is in excess of 17-34 μg/100 ml.